Deteksi Dini Derajat Kesadaran Menggunakan Pengukuran Nilai Kritis Mean Artery Pressure - Martono Martono; Sudiro Sudiro; Satino Satino (Universitas Airlangga, 2016)
Introduction: The Impact of the trauma cranio cerebral can affect the volume autoregulation disorders any intracranial disease that consists of the brain and cerebrospinal fluid and the blood in the veins. The changes one of the volume without followed the response of compensation from the other factors will cause overt increased intracranial pressure changes and the amount of blood flow from the systemic circulation required to give oxygen and glucose intake to the metabolism of the brain. One of the things that is very important in nursing nursery on patients with injury head is to maintain the adequacy of Mean Artery Pressure cerebral. This research aims to know the adequacy of critical value mean artery pressure in detecting the level of consciousness in patients who suffered injury on the head.Methods: This research using explanatory design research with cross sectional approach that explains the influence and the prediction of the adequacy of the critical value mean arteria pressure against the degree of awareness in patients with injury head which numbered 34 samples. This research statistics tests using simple regression.Results: The results of the study showed that there is a positive influence critical value mean artery pressure against the degree of awareness that indicated the value of p=0.00<0.05 and value of mean artery pressure is able to detect the level of consciousness patients injury head of 77.8%.Discussion: Increased critical value mean arterial pressure is more than 65 mmHg can improve mikrosirkulasi and autoreglasi brain, so that prevent the decline of awareness in patients with wounds of the head.